(untitled) (Tikrit Journal of Pharmaceutical Sciences, 2023)
Aims: To compare parameters in Iraqi subjects with Metabolic syndrome , without metabolic syndrome, and comparing the parameters between two groups of the patients with metabolic syndrome the first group without drug but the second group were using drug. Method: Study were carried on 60 Iraqi Subjects ,40 of them with metabolic syndrome ( 20 of the patient did not use any drugs while 20 of the patient used drugs and the rest were control group) . All Study subjects were taken from Balad hospital .The study measured age , Wc , DBP , SBP , FBG , TG , Cholesterol, HDL , LDL , VLDL , and UA. Results: There are high significant difference between control and study group regarding the following parameters age, Wc , DBP, SBP, FBG ,TG ,HDL, and UA where P values were less than (0.05) .but Cholesterol, LDL, VLDL were more than 0.05 no significant. Comparing treated group with not treated group, found that high significant for DBP , SBP ,FBG ,TG and VLDL with P value less than (0.05) but age , WC ,Cholesterol , HDL , LDL and UA with p value more than (0.05) no significant. Conclusions: In metabolic syndrome WC, blood pressure, FBG and TG were increased but HDL was decreased. All parameters decreased when used the drug in the metabolic syndrome. Except HDL increased after used the drug.